On Open House International, Open Building Approach and Nicholas Wilkinson - Hurol, Yonca; Salama, Ashraf (Emerald Publishing, 2020)
The purpose of this study is to identify the transformations, which have taken place in Open House International (OHI) throughout its life span of 44 years while highlighting key aspects of research and publication trends. For this purpose, OHI volumes were grouped for chronological examination. Each group was subsequently analysed to establish the technical, academic and philosophical underpinnings, which have evolved throughout more than four decades. The findings of this research demonstrate that OHI was a dynamic journal and has maintained its connection with the open building approach following the decline of Nicholas Wilkinson’s health in 2015. This analysis can be used in establishing the future direction of the journal and similar journals. It can also be used as a source of data for longitudinal research on the topics of open building, housing, the urban environment and the associated trends. The open building approach is still active in 2020 and this research presents one dimension of the history of the open building approach.
This article is about the history of the academic journal Open House International, which was found by Nicholas Wilkinson in 1975.
Keywords: Open House International; Open Building; architecture